Preparation, corrosion, and wear resistance of Ni‐Mo/Al composite coating reinforced with Al particles. (15th November 2016) - Mousavi, R.; Bahrololoom, M.E.; Deflorian, F.
Abstract: In this research, Ni‐Mo/Al composite coatings were deposited from a citrate bath containing Al metallic particles. The impact of Al particle content in the bath on the microstructure, texture, thickness, current efficiency, wear and corrosion behaviors of Ni–Mo/Al coatings was surveyed. The [200] preferred orientation developed slowly to the [111] orientation with increasing Al loadings in the bath. The results showed that electroplating at 40 °C and citrate ion concentration of 0.15 M had the highest current efficiency and produced a dense coating free of cracks. Because of the presence of Mo, the morphology of the matrix changed from a regular pyramidal structure for Ni‐Al composite coatings to cauliflower for Ni‐Mo/Al composite coatings. The wear resistance of coatings decreased due to the increase of Al content in the coating. The polarization tests indicated that the corrosion resistance of the Ni‐Mo/Al composite coating was enhanced by adding Al metal particles. This was due to the increase of Al content and decrease of the grain size of the coatings. Graphical abstract: Highlights: Electrodeposition of Ni-Mo/Al composite coating as a new composite coating is possible. The Addition of Al metallic particles to the Ni-Mo alloy coatings can improve the corrosion resistance of coatings. The current efficiency is reached to a maximum and then decreased by increasing Al loading in the bath. There is an inverse correlation between the wear behavior and surface hardness which obeys the Archard's law.